Proper Glyphosate Application at Post-anthesis Lowers Grain Moisture Content at Harvest and Reallocates Non-structural Carbohydrates in Maize - Zhao, Linmao; Xie, Liuyong; Huang, Jingli; Su, Yingchun; Zhang, Chunqing (Frontiers in Plant Science, 2020)
Glyphosate (GP)-based herbicides have been widely applied to crops for weed control and pre-harvest desiccation. The objective of this research was to evaluate the effects of pre-harvest GP application on maize or how it physiologically alters this crop. Here, we applied four GP treatment (Control, GP150, GP200 and GP250) on maize lines of Z58 and PH6WC belonging to different maturity groups at grain-filling stages form DAP30 to DAP45. GP application significantly decreased the grain moisture content at harvest by 22 35% for Z58 and by 15 41% for PH6WC. However, the responses of grain weight to glyphosate vary with inbred lines and application time. A high concentration of glyphosate (GP250) reduced the grain weight of Z58 and low concentrations (GP150 and GP200) did not affect, while the grain weight of PH6WC significantly decreased under glyphosate treatment. In summary, our results revealed that timely and appropriate GP application lowers grain moisture content without causing seed yield and quality loss. GP application adversely affected photosynthesis by promoting maturation and leaf senescence. Meanwhile, it also enhanced nonstructural carbohydrate (soluble sugars and starch) remobilization from the vegetative organs to the grains. Hence, GP treatment coordinates plant senescence and assimilate remobilization. RNA sequencing revealed that glyphosate regulated the transcript levels of sugar signaling-related genes and induced assimilate repartitioning in grains. This work indicates the practical significance of GP application for maize seed production and harvest, which highlights the contributions of source-sink communication to maize yield in response to external stress or pre-harvest desiccant application.